A contribución de Alonso Zamora Vicente - Fernández Rei, Francisco (Revista de Filología Románica, 2008)
This article proposes a journey through the scientific papers written by Alonso Zamora Vicente which are dedicated to the Galician dialectology, especially those who study the seseo and the gheada circumstances.